2021
DOI: 10.5599/jese.956
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 4-nitrophenol using MoO3 loaded glassy carbon electrode via electrochemical sensing approach

Abstract: In order to raise possible ways of MoO3 synthesis and improve its existing applications, MoO3 nanomaterial was successfully synthesized through the solvo-hydrothermal route by utilizing a mixture of ionic liquid (1-butyl-3-methylimidazolium bromide) as a solvent, and water as co-solvent in 1:1 ratio. The morphology and structural parameters of IL-as­sisted MoO3 product were examined by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Chemical modification of electrodes is a quite useful technique for detecting organophosphorus toxins [64]. Such technologies are appropriate alternatives to increase the electron transfer rate in electrochemical sensors [65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modification of electrodes is a quite useful technique for detecting organophosphorus toxins [64]. Such technologies are appropriate alternatives to increase the electron transfer rate in electrochemical sensors [65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%
“…However, the widespread application of some of these methods has been limited by their complex operation and high cost. Electrochemical determinations have been shown to be more appropriate for analyte analysis [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], owing to commendable merits such as cost-effectiveness, narrow LOD, higher sensitivities, wide potential window, short analysis time, and ease to renew the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a need for the small volume of solution for electrochemical determination, which is indeed interesting in terms of green chemistry [ 39 , 40 ]. Chemically modified electrodes (CMEs) are the result of the intentional fixation of a modifying agent on the surface of electrode by various physical and chemical methods [ 41 , 42 ]. Many studies have shown that improvements in the sensitivity and selectivity of electrochemical sensors are achieved due to modifications of the electrode surface [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%